THE ARGUMENT-PREDICATIVE STRUCTURE IN LEGAL DISCOURSE - Mykhailova, O.V. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching)
The article focuses on the analysis of the argument-predicative clause structure in the official type of legal discourse with the purpose to establish mental schemes verbalized by the participants of legal communication. The application of the cognitive approach allows the explanation of the syntactic peculiarities of legal discourse. Key words: adjuncts, circonstants, clause, legal discourse, mandatory syntactic argument, mental scheme, the argument-predicative structure. Михайлова О.В. Аргументно-предикатна структура в юридичному дискурсі. В статті розглядаються питання пов’язані з реалізацією аргументно-предикатної структури елементарного речення в текстах ділового юридичного дискурсу. Мета статті – встановити ментальні схеми за якими учасники правової комунікації висловлюють свої наміри. Застосування когнітивного підходу дозволяє пояснити синтаксичні особливості організації юридичного дискурсу. Ключові слова: ад’юнкти, актанти, аргументно-предикатна структура, елементарне речення, ментальна схема, сірконстанти, юридичний дискурс. Михайлова Е.В. Аргументно-предикатная структура в юридическом дискурсе. В статье рассматриваются вопросы, связанные с реализацией аргументно-предикатной структуры элементарного предложения в текстах делового вида юридического дискурса. Цель статьи – установить ментальные схемы, в соответствии с которыми, участники правовой коммуникации передают определенные смыслы. Применение когнитивного подхода позволяет объяснить синтаксические особенности организации юридического дискурса. Ключевые слова: адъюнкты, актанты, аргументно-предикатная структура, элементарное предложение, ментальная схема, сирконстанты, юридический дискурс.